Henry James. - Edel, Leon, 1907-1997 (University of Minnesota pamphlets on American writers, 1960)
Henry James - American Writers 4 was first published in 1960. Minnesota Archive Editions uses digital technology to make long-unavailable books once again accessible, and are published unaltered from the original University of Minnesota Press editions.